2000
DOI: 10.2307/2656852
|View full text |Cite
|
Sign up to set email alerts
|

Floral dimorphism, pollination, and self‐fertilization in gynodioecious GERANIUM RICHARDSONII (Geraniaceae)

Abstract: The selective maintenance of gynodioecy depends on the relative fitness of the male-sterile (female) and hermaphroditic morphs. Females may compensate for their loss of male fitness by reallocating resources from male function (pollen production and pollinator attraction) to female function (seeds and fruits), thus increasing seed production. Females may also benefit from their inability to self-fertilize if selfing and inbreeding depression reduce seed quality in hermaphrodites. We investigated how difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
63
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 52 publications
9
63
0
Order By: Relevance
“…More generally, our results complement and partly confirm conclusions drawn by studies that used other methodological approaches to investigate the evolutionary dynamics driving the evolution of gynodioecy and found variation in sex ratio among populations that fits expectations under balancing selection (for example, Dufay et al (2009) in Beta vulgaris) and empirical evidence for frequency-dependent individual reproductive success, that is a necessary condition for such dynamics to occur (for example, Graff (1999) in Sidalcea malviflora; Williams et al (2000) in Geranium richardsonii; McCauley and Brock (1998) and Miyake and Olson (2009) The non-gynodioecious sister species to which the nucleotide diversity of S. nutans was compared in this study is dioecious (with males and females). This reproductive system has evolved many times independently in flowering plants (reviewed by Renner and Ricklefs (1995)).…”
Section: Discussionsupporting
confidence: 77%
“…More generally, our results complement and partly confirm conclusions drawn by studies that used other methodological approaches to investigate the evolutionary dynamics driving the evolution of gynodioecy and found variation in sex ratio among populations that fits expectations under balancing selection (for example, Dufay et al (2009) in Beta vulgaris) and empirical evidence for frequency-dependent individual reproductive success, that is a necessary condition for such dynamics to occur (for example, Graff (1999) in Sidalcea malviflora; Williams et al (2000) in Geranium richardsonii; McCauley and Brock (1998) and Miyake and Olson (2009) The non-gynodioecious sister species to which the nucleotide diversity of S. nutans was compared in this study is dioecious (with males and females). This reproductive system has evolved many times independently in flowering plants (reviewed by Renner and Ricklefs (1995)).…”
Section: Discussionsupporting
confidence: 77%
“…This difference was similar for naturally pollinated flowers, except that those flowered four days shorter. Other studies on naturally pollinated flowers also showed an extended period of stigma lifespan for females (Ashman and Stanton, 1991;Petterson, 1992), and it has been suggested (but not measured) for several other species, including Geranium (Shykoff, 1992;Williams et al, 2000;Rodriguez-Riano and Dafni, 2007;Molano-Flores and Faivre, 2015). Whereas these other studies may indicate that extended maximum stigma lifespan in females is a general phenomenon among protandrous gynodioecious species, the differences in stigma lifespan may also be explained by the higher visitation rates observed for hermaphrodites.…”
Section: Discussionmentioning
confidence: 47%
“…richardsonii (Williams et al, 2000), depends on whether flower visitation and/or pollination have an effect on the duration of the floral phases. Pollinators cannot only induce senescence, shortening the female phase, but by removal of pollen they can also induce the female phase in some protandrous species (Evanhoe and Galloway, 2002;Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations